SIMULATION MODEL AS A TOOL TO OPTIMIZE THE OPERATION OF THE PROCESSLINE FOR MANUFACTURING CONSTRUCTION PRODUCTS - Akishev Karshyga; Bykov Petr; Aringazin Kapar; Zhanserik Shoshay; Karpov Valeriy (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The article discusses the practical application of a method of simulation modeling for the object of studying the processline for manufacturing construction products using industrial wastes. The purpose of the study is to optimize the operation of the processline for manufacturing construction products using industry-related wastes and to develop the tools for calculating the productive efficiencyof the processline of production, with variable nomenclature of construction products, concrete mix composition, scenarios of production technology, with the possibility of determining raw material resources of an enterprise.